Giant magnetization of a superconductor-two-dimensional electron gas-superconductor structure: Carbon nanotubes, quantum wires and Luttinger liquid - Romanovsky, I.A.; Bogachek, E.N.; Krive, I.V.; Landman, Uzi (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Superconductivity induced phase-controlled mesoscopic magnetic effects in a two-dimensional electron gas that bridges two superconducting reservoirs are investigated. Giant paramagnetic response of the junction, occuring at certain values of the phase difference of the order parameter, is predicted. A geometricallysimilar system, consisting of a graphene ribbon stretched between two superconducting leads, is also considered.The magnetic effects in this system are found to be small and the difference between the magnetic properties of the two systems is discussed.